Conceptualizing physical activity parenting practices using expert informed concept mapping analysis - Louise C. Mâsse; Teresia M. O'Connor; Andrew W. Tu; Sheryl O. Hughes; Mark R. Beauchamp; Tom Baranowski; Physical Activity Parenting Expert Group (BMC, 2017)
Abstract Background Parents are widely recognized as playing a central role in the development of child behaviors such as physical activity. As there is little agreement as to the dimensions of physical activity-related parenting practices that should be measured or how they should be operationalized, this study engaged experts to develop an integrated conceptual framework for assessing parenting practices that influence multiple aspects of 5 to 12 year old children's participation in physical activity. The ultimate goal of this study is to inform the development of an item bank (repository of calibrated items) aimed at measuring physical activity parenting practices. Methods Twenty four experts from 6 countries (Australia, Canada, England, Scotland, the Netherlands, & United States (US)) sorted 77 physical activity parenting practice concepts identified from our previously published synthesis of the literature (74 measures) and survey of Canadian and US parents. Concept Mapping software was used to conduct the multi-dimensional scaling (MDS) analysis and a cluster analysis of the MDS solution of the Expert's sorting which was qualitatively reviewed and commented on by the Experts. Results The conceptual framework includes 12 constructs which are presented using three main domains of parenting practices (neglect/control, autonomy support, and structure). The neglect/control domain includes two constructs: permissive and pressuring parenting practices. The autonomy supportive domain includes four constructs: encouragement, guided choice, involvement in child physical activities, and praises/rewards for their child's physical activity. Finally, the structure domain includes six constructs: co-participation, expectations, facilitation, modeling, monitoring, and restricting physical activity for safety or academic concerns. Conclusion The concept mapping analysis provided a useful process to engage experts in re-conceptualizing physical activity parenting practices and identified key constructs to include in measures of physical activity parenting. While the constructs identified ought to be included in measures of physical activity parenting practices, it will be important to collect data among parents to further validate the content of these constructs. In conclusion, the method provided a roadmap for developing an item bank that captures key facets of physical activity parenting and ultimately serves to standardize how we operationalize measures of physical activity parenting.